Foundational Small Ruminant Management and Husbandry - Christa L. Kirby; Allie L. Williams; Laura H. Bennett; Bridget Stice; Brittany N. Diehl (EDIS, 2025)
This article is meant to serve as an overview of small ruminant husbandry practices, which include basic nutrition, health, and preventative management concepts. Written by Christa L. Kirby, Allie L. Williams, Laura H. Bennett, Bridget Stice, and Brittany N. Diehl, and published by the UF College of Veterinary Medicine, UF/IFAS Extension, June 2025.